PENGARUH PENAMBAHAN DOSIS RAFINOSA DALAM PENGENCER SITRAT KUNING TELUR TERHADAP MOTILITAS, PERSENTASE HIDUP DAN ABNORMALITAS SPERMATOZOA SAPI ONGOLE - Pubiandara, Sintha; Suharyati, Sri; Hartono, Madi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The research which was conducted in the Regional Technical Services Unit Lampung Regional Artificial Insemination Centres, Regency Terbanggi Â Besar, Central Lampung Regency, Lampung Province on 19-20 May 2016, aims to determine the effect of dose rafinosa in egg yolk citrate diluents on motility, percentage of live sperm and abnormal spermatozoa Ongole. The experimental usedÂ is completely randomized design with 6 treatments rafinosa dose (0.5%; 1%; 1.5%; 2%; 2.5%; 3%) in the egg yolk citrate diluent and each treatment be repeated 4 times. The data obtained were analyzed using analyzed variety at significance level of 5% or 1% then for variables that significantly undergone orthogonal polynomial test to determine the optimum dose rafinosa. The results showed that the addition of a diluent doses rafinosa in egg yolk citrate is not significantly different (P> 0.05) on the percentage of live sperm in prefreezing and post thawing motillity; on motility and sperm abnormalities in the equilibration, prefreezing and PTM. Extra doses of raffinose in egg yolk citrate highly significant (P <0.01) on the percentage living on equilibration sermatozoa patterned quadratic. Found that the addition rafinosa at equilibration was highly significant (P <0,01) to live spermatozoa with Ã = 66.49 + 17,94x-4,23x2 with the optimum value of 2.1%.Â Keywords: Â Rafinose , Motility, Percentage of Live, Abnormal Spermatozoa, Ongole CattleÂ